2011
DOI: 10.4236/psych.2011.29135
|View full text |Cite
|
Sign up to set email alerts
|

The Survival Processing Memory Effect Should Generalise to Source Memory, but It Doesn’t

Abstract: Numerous studies have shown that words judged for their relvance to a scenario of survival are remembered better than words from lists processed differently. Survival processing is even more effective than many mnemonic techniques. This has been interpreted as an evolutionary design feature of memory. It is argued that such a survival effect should be even more pronounced in remembering the context or source of the information. Two experiments used a source monitoring paradigm. Both studies did not find any ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 39 publications
0
22
2
Order By: Relevance
“…The elaborative-encoding view advocated here could also help to integrate previous findings on source memory. For instance, in the study of Bröder et al (2011), participants rated the relevance of items according to their relevance in a standard survival processing scenario. The words were placed at different positions at the screen, but location was entirely irrelevant to the rating task.…”
Section: Discussionmentioning
confidence: 99%
“…The elaborative-encoding view advocated here could also help to integrate previous findings on source memory. For instance, in the study of Bröder et al (2011), participants rated the relevance of items according to their relevance in a standard survival processing scenario. The words were placed at different positions at the screen, but location was entirely irrelevant to the rating task.…”
Section: Discussionmentioning
confidence: 99%
“…Although prior research has shown a survival processing advantage for item memory (Scofield et al, 2018), less is known about the effects of survival processing on context memory (i.e., memory for peripheral episodic details during study). The limited studies on survival processing effects on context have produced mixed results, with some evidence in support of context memory improvements compared to controls (Nairne et al, 2012;Clark and Bruno, 2016;Kroneisen and Bell, 2018;Misirlisoy et al, 2019;Zhang et al, 2020), whereas others have found no such benefits (Bröder et al, 2011;Savine et al, 2011;Nairne et al, 2015;Hou and Liu, 2019). In a study reporting a survival processing context memory advantage, participants were shown items in various locations on a computer screen and asked to process them in either a survival or scavenger hunt condition (Nairne et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Following these findings, there has been a surge of interest in adaptive memory. Research appears to show consistently that survival processing is a more effective encoding task than other types of semantic processing paradigms, including imagery and selfreference (Kang, McDermott & Cohen, 2008;Nairne, Pandeirada & Thompson, 2008;Nairne, Pandeirada, Gregory & Van Arsdall, 2009;Burns, Burns & Hwang, 2011;Otgaar et al, 2011;Soderstrom & McCabe, 2011;Seamon et al, 2012;Bröder, Krüger & Schütte, 2011;Klein, 2012;Nairne, VanArsdall, Pandeirada & Blunt, 2012;Nouchi & Kawashima, 2012;Howe & Otgaar, 2013;Pandeirada, Pinho & Faria, 2014; but for exceptions, see Butler, Kang & Roedier, 2009;Klein, Robertson & Delton, 2010;Klein, Robertson & Delton, 2011). All in all, it has been suggested that survival processing may be "the 'best of the best' of known encoding procedures" (Nairne, Pandeirada & Thompson, 2008, p. 180).…”
Section: Introductionmentioning
confidence: 99%